Anionic Polymerization of Divinylbenzenes Possessing Methoxy Group. Issue 12 (8th February 2017) - Otake, Kohei; Matsumoto, Masayoshi; Tanaka, Shunsuke; Uchida, Satoshi; Goseki, Raita; Hirao, Akira; Ishizone, Takashi
Abstract : Anionic polymerization of methoxy‐substituted divinylbenzene derivatives, three asymmetric 1, 2‐, 1, 3‐, and 1, 4‐divinylbenzenes, and two symmetric 1, 3‐divinylbenzenes, is performed with oligo(α‐methylstyryl) anion in tetrahydrofuran. The asymmetric divinylbenzenes undergo the living polymerization in the presence of alkoxide additives to give the well‐defined polymers. On the other hand, the polymerization of the symmetric divinylbenzenes gives the polymers with ill‐controlled structures. Abstract : The anionic polymerizations of novel methoxy‐substituted divinylbenzenes possessing nonequivalent vinyl groups, such as 2‐methoxy‐1, 4‐divinylbenzene (1 ), 4‐methoxy‐1, 2‐divinylbenzene (2 ), and 4‐methoxy‐1, 3‐divinylbenzene (3 ), are carried out with oligo(α‐methylstyryl)lithium (αMSLi) in the presence of potassium tert ‐butoxide ( t BuOK) in tetrahydrofuran at −78 °C. The poly(1 )–poly(3 ) obtained with αMSLi/ t BuOK are completely soluble and possess predicted molecular weights and narrow molecular weight distributions (MWD) ( M w / M n < 1.1). On the other hand, the corresponding symmetrical divinylbenzenes, 2‐methoxy‐1, 3‐divinylbenzene (4 ) and 5‐methoxy‐1, 3‐divinylbenzene (5 ), undergo anionic polymerization to afford polymers with broad MWDs, indicating the occurrence of a serious intermolecular side reaction. The stability of the propagating carbanion derived from1–3 is demonstrated by the quantitative efficiency of the sequential copolymerization with tert ‐butyl methacrylate. The chemical structure of the repeating unit of poly(1 )–poly(3 ) is characterized by the 1 H and 13 C nuclear magnetic resonance measurements, suggesting that the polymerization of asymmetrical divinylbenzenes, 1 –3, proceeds mainly on one of the nonequivalent vinyl groups. The electronic and steric effects of the electron‐donating methoxy group play important roles in realizing the living anionic polymerization of these divinylbenzenes. The resulting poly(1 )–poly(3 ) show a thermal cross‐linking property over 300 °C, indicating the reactivity of the residual pendant vinyl group in each repeating unit.